Relationship between Perceived Supervisor Support (PSS) and Organizational Commitment (OC) among academicians in UiTM Melaka / Nani Shuhada Sehat, Mazida Ismail and - Sehat, Nani Shuhada; Ismail, Mazida; Daud, Siti Rohana (2011)
Nowadays, education becomes one of the most important aspects in our life. Every human being is being educated from primary and secondary school until higher educational institution. Therefore, the role as academician was one of the vital role to ensure the needs of learning institution and their student can be fulfilled. In order to maintain the number of academicians, the support of the supervisor is very crucial to maintain the commitment of academicians especially in higher learning institution. The purpose of this study is to examine the relationship between perceived supervisor support (PSS) and organizational commitment (OC) and to determine which types of organizational commitment namely affective commitment (AFFOC), normative commitment (NORMOC) and continuance commitment (CONTOC) was most influenced by PSS among academicians in UiTM Melaka. Supervisor in UiTM Melaka was called as coordinator. The questionnaire distributed randomly to 200 academicians in UiTM Melaka but only 119 were returnable, completed and useful. Data from 119 academicians were analyzed using Statistical Package for Social Science (SPSS). Pearson Correlation test were be used to test the relationship between PSS and all three OC and regression analysis were used to determine which types of three OC was most influenced by PSS among academicians in UiTM Melaka. All variables are proven reliable after going through reliability test. The findings suggest that PSS has positive relationship with AFFOC, CONTOC and NORMOC but only AFFOC and NORMOC has significant relationship with PSS. Meanwhile, all the three OC was influenced by PSS among respondents in UiTM Melaka. It concludes that organizational commitment all the academicians in UiTM Melaka very much dependent in perceived supervisor support that they received.